A Study on the Trainee Teachers' Self Assessment in Physical Education Teaching Skills and its Effect on their Academic Achievement - İNAN, MEHMET (SAGE Publications Ltd, 2010)
Self-assessment is described as the students' decision about their own development and study according to some criteria. The sample group consists of 170 students of the 3rd graders of the Primary School Teachers Training Department. The data collection tools are a “Self-Assessment Checklist” and the students' academic grades of the related course. The student teachers seem to perceive that they need some development in all skill areas except “the communication skills”. The female subjects have more positive perception about their competency compared to males. As a result of the research, it has been determined that except contributing to the quality of the teaching, self-assessment has no effect on the “product”, in other words “class achievement”. © 2010 A B Academic Publishers Printed in Great Britain.